Optimization of the Spatial Configuration of Local Defects in Phononic Crystals for High Q Cavity - Reyes, Delfino; Martínez, David; Mayorga, Miguel; Heo, Hyeonu; Walker, Ezekiel; Neogi, Arup (Frontiers in Mechanical Engineering, 2020)
Defects can be introduced within a 2-D periodic lattice to realize phononic cavities or phononic crystal (PnC) waveguides at the ultrasonic frequency range. The arrangement of these defects within a PnC lattice results in the modification of the Q factor of the cavity or the waveguide. In this work, cavity defects within a PnC formed using cylindrical stainless steel scatterers in water have been modified to control the propagation and Q factor of acoustic waveguides realized through defect channels. The defects channel based waveguides within the PnC were configured horizontally, vertically, and diagonally along the direction of the propagation of the acoustic waves. Numerical simulations supported by experimental demonstration indicate that the defect-based waveguide's Q factor is improved by over 15 times for the diagonal configuration compared to the horizontal configuration. It also increases due to an increase in the scatterers' radius, varied from 0.7 -0.95 mm.